Improving the Bit Error Rate Performance of Free Space Optical Communication due to Atmospheric Turbulence Effect using New Double Multiple-Input Multiple-Output Technique - Abdul Rahman, Kram; Tom, A. L. (2020)
This paper focus on mitigating the atmospheric turbulence effect in free space optical (FSO) communications by using double multiple input multiple output (DMIMO)technique. This technique is an enhancement of the conventional multiple input multiple output (MIMO) technique in improving the performance of FSO system. The combination of double MIMO with differential detection mode at the receiver resulting in superior modulation against the turbulence especially in reducing the scintillation index, enhance the power received and improve the threshold signal level. The analysis result shows that under strong turbulence conditions, the bit error rate can be improved by 20 percent in terms of free space optical distance propagation.